Endoscopic papillectomy for early ampullary tumors: long-term results from a large multicenter prospective study - Napoleon, Bertrand; Gincul, Rodica; Ponchon, Thierry; Berthiller, Julien; Escourrou, Jean; Canard, Jean-Marc; Boyer, Jean; Barthet, Marc; Ponsot, Philippe; Laugier, René; Helbert, Thierry; Coumaros, Dimitri; Scoazec, Jean-Yves; Mion, François; Saurin, Jean-Christophe; null (Endoscopy, 2014)
Background and study aims: Endoscopic papillectomy of early tumors of the ampulla of Vater is an alternative to surgery. This large prospective multicenter study was aimed at evaluating the long-term results of endoscopic papillectomy. Patients and methods: Between September 2003 and January 2006, 10 centers included all patients referred for endoscopic papillectomy and meeting the inclusion criteria: biopsies showing at least adenoma, a uT1N0 lesion without intraductal involvement at endoscopic ultrasound (EUS), and no previous treatment. A standardized endoscopic papillectomy was done, with endoscopic monitoring with biopsies 4 – 8 weeks later where complications were recorded and complementary resection performed when necessary. Follow-up with duodenoscopy, biopsies, and EUS was done at 6, 12, 18, 24 and 36 months. Therapeutic success was defined as complete resection (no residual tumor found at early monitoring) without duodenal submucosal invasion in the resection specimen in the case of adenocarcinoma and without relapse during follow-up.Results: 93 patients were enrolled. Mortality was 0.9 % and morbidity 35 %, including pancreatitis in 20 %, bleeding 10 %, biliary complications 7 %, perforation 3.6 %, and papillary stenosis in 1.8 %. Adenoma was not confirmed in the resection specimen in 14 patients who were therefore excluded. Initial treatment was insufficient in 9 cases (8 carcinoma with submucosal invasion; 1 persistence of adenoma). During follow-up, 5 patients had tumor recurrence and 7 died from unrelated diseases without recurrence. Finally, 81.0 % of patients were cured (95 % confidence interval 72.3 % – 89.7 %). Conclusion: Endoscopic papillectomy of selected ampullary tumors is curative in 81.0 % of cases. It must be considered to be the first-line treatment for early tumors of the ampulla of Vater without intraductal invasion.